Perancangan Aplikasi Game Maze Escape Dengan Menerapkan Algoritma Greedy Untuk Pencarian Jalur Terpendek - Nanda Sopianto; Mesran Mesran (STMIK Budi Darma, 2021)
In modern times games that require extensive space and spend a lot of resources such as the maze game are starting to disappear. But the development of technology made games such as maze escape develop in the form of computer simulations. The purpose of this study is to design a game that can be played to fill free time and eliminate boredom and simultaneously train the player's brain. To determine the most optimal route, the route that has the shortest distance is using the Greedy algorithm approach. The Greedy algorithm is an algorithm that solves problems step by step and is one method in optimization problems. The approach used in the Greedy algorithm is to make a choice that looks to provide the best gain, namely by making a choice of local optimum at each step and is expected to get a global optimum solution.